KZN WIMPY FRANCHISEE VIEWS ON THE FAMOUS BRANDS ACQUISITION - Du Plooy, Georgina (The IIE, 2019)
This study is qualitative in nature, and aims to identify the key views KZN Wimpy franchisees held of the Famous Brands acquisition which took place in 2003. The study will analyse Wimpy’s brand equity, the impact of the acquisition on the franchisees, and the effectiveness of the communication used regarding the acquisition. The information gathered in this study was collected through the use of qualitative methods, including a pilot study, questionnaires and interviews. The key findings and insights within this research led to themes being identified. Through the research conducted, it was concluded that the franchisees were not communicated with effectively, had various concerns which they did not have the opportunity to address, and that the Wimpy brands’ equity has positively been affected due to the acquisition. Recommendations have been made which will alleviate the concerns franchisees faced due to the acquisition, as well as for how future acquisitions can gain the support of the franchisees prior to publicly announcing the acquisition.
Keywords: Brand; Brand communication; Brand equity; Business acquisition; Franchise; Organisation culture